Identification and Quantification of Sucrose Losses in the Final Effluent of the Sugar-making Process at the Riopaila Castilla Sugar Mill (Castilla plant) - Corrales Correa, Efrén; Garzón García, Guillermo (Ingeniería Solidaria, 2014)
This article stems from the graduate project “Identification and Quantification of Sucrose Losses in the Final Effluent of the Sugar-making Process at a Sugar Mill” (“Identificación y cuantificación de pérdidas de sacarosa en el efluente final del proceso de elaboración de azúcar en un ingenio azucarero”) carried out at the Universidad Santiago de Cali. The objective was to identify and quantify sucrose losses in the manufacturing effluent at the Castilla plant of the Riopaila Castilla sugar mill. The research problem stemmed from interest in making use of the large quantity of sucrose lost during the sugar making process, amounting to approximately 1.5 billion COP per year. The results were a decrease in sucrose losses that earned the mill first place, with the lowest sucrose losses in the entire Colombian sugar sector; the creation of six new jobs (losses inspectors); a decrease in environmental impact through reduction of polluting sucrose in the final effluent; and better handling to control sucrose in the final effluent.
Keywords: sucrose; flow; brix; clarified juice